Effects of a proteasome inhibitor on the NF-κB signalling pathway in experimental osteoarthritis. (October 2013) - Quan, R; Huang, Z; Yue, Z; Xin, D; Yang, D; Pan, J; Zhang, L
Abstract : Objectives: To evaluate the effects of the proteasome inhibitor MG-132 on the expression of nuclear factor (NF)-κB p65, inhibitor (I)-κB, tumour necrosis factor (TNF)-α, and interleukin (IL)-1β in the cartilage and synovial tissues of rats with osteoarthritis (OA), and to investigate the role that the ubiquitin/proteasome system (UPS) plays in the OA process. Method: A total of 144 adult male Sprague Dawley rats were randomly assigned to four groups: anterior cruciate ligament transaction (ACLT) + MG-132 (ACLT/M), ACLT + dimethylsulfoxide (ACLT/D), sham surgery (Sham), and naïve + MG-132 (naïve/M). Pathological morphology was undertaken. mRNA expression levels of NF-κB p65, I-κB, TNF-α, and IL-1β were determined using real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR). The activities of the 20S proteasome chymotrypsin-like and peptidylglutamyl-peptide hydrolase-like enzymes were measured using fluorospectrophotometry. Results: The Mankin scores at all time points in ACLT/M rats were significantly lower than those in ACLT/D rats (p < 0.05). Despite the NF-κB p65 in the synovial tissue at 2 weeks after surgery and IL-1β in the cartilage tissue at 12 weeks after surgery, mRNA expression levels of NF-κB p65, IL-1β, and TNF-α at other time points in ACLT/M were significantly lower than those in ACLT/D (p < 0.05). mRNA levels of I-κB in the cartilage tissue in ACLT/M were significantly higher than those in ACLT/D at 2 weeks after surgery (p < 0.05). mRNA levels of I-κB in the synovial tissue in ACLT/M were higher than those in ACLT/D at all time points, and the difference was significant at 4 weeks after surgery (p < 0.05). MG-132 decreased the activities of the 20S proteasome chymotrypsin-like and peptidylglutamyl-peptide hydrolase-like enzymes in the cartilage and synovial tissues of rats. Conclusions: The proteasome inhibitor MG-132 delays the progress of OA by alleviating synovial inflammation and protecting the articular cartilage tissue.